Covid-19 Pandemic: Impact on skill improvement of the Indonesian teachers in using online learning applications - Zuardin Arif; Al Azhar (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
The Covid-19 outbreak was first confirmed to have infected 2 Indonesians on March 2, 2020. Indonesian schools began to close in mid-March, face-to-face teaching, and the learning process turned into online learning. Since then, the use of online learning applications increased significantly. The objective of this study was to investigate the benefits of using online learning applications for Indonesian teachers. Data collection by distributing online questionnaires in Google form to teachers joining online training, online exam preparation questions organized by the LPPPTK KPTK, opened the link on May 14 and closed on May 27, 2020. 911 participants giving responses came from 32 provinces of 34 in Indonesia. Data were processed with SPSS software version 26.0. A univariate analysis was chosen to describe the frequency distribution and percentage of each variable. Spearman's correlation coefficient, r, was used to evaluate the association among the variables, and a two-tailed p < 0.05 was considered the statistically significant relationship between sample characteristics, the benefit of online training substance, and the developing teacher skills in using several online learning applications during the Covid-19 pandemic. Respondent areas mapping used geographic information system (GIS), assisted by ArcGIS 10.3 software. The results confirmed that 748 (82.11%) teachers said that more learning applications were mastered during the pandemic compared to before Covid-19 infection. The gender, education, school level, and region didn’t influence skill improvement in using online learning applications. But it was largely determined by the online training substance, the significance value < 0.05, and the degree of relationship 0.90.